PENINGKATAN HASIL BELAJAR MATA PELAJARAN MUATAN LOKAL KETERAMPILAN TATA BUSANA MELALUI METODE PELATIHAN BERBASIS INKUIRI - Siti Maemunatun (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2016)
The purpose of this study is toimprove students' learning achievement of SMPNegeri 1 Pulokulon Grobogan Regency CentralJava Province with inquiry based method on thesubject Local content of dressing skills. Thisresearch includes a classroom action researchconsisting of planning, action, observation, andreflection. The subjects of the study were thestudents of class VIII A. Techniques of datacollection using the method of documentation,test, observation. The technique of data analysisusing a descriptive method by comparingstudent learning outcomes before action andafter an action. The results of the research inthe first cycle obtained 35% of students arecomplete and 65% of students have not beencompleted. In the second cycle do someimprovements in the process of implementationof learning guided inquiry based trainingmethod (guided inquiry). Data cycle II resultsobtained 100% increase in students complete, orlearning outcomes meet the standard value